Role of autophagy in regulation of genome stability. - Ng, Yan Ting. (2013)
Genomic instability is a fundamental component of cancer and aging. Defects in autophagy, a lysosome-mediated degradation pathway, have recently been associated with genomic instability but the exact mechanisms underlying this association remain ill-defined. Here, we have identified a role of autophagy in the regulation of genome stability through the modulation of condensin I, a nuclear complex that drives chromosome condensation during mitosis. CAP-G, a condensin I regulatory subunit, was found to be indirectly influenced by the activity of autophagy. We observed a distinct reduction in CAP-G levels in autophagy-deficient cells. This suggests that the physiological functions of condensin I in facilitating the condensation of mitotic chromosomes during mitosis and in DNA repair may be compromised when autophagy becomes defective thereby contributing to genome alterations. In support of this, we have observed higher susceptibility towards DNA damage and abnormal mitotic chromosome structures in autophagy-deficient cells. Our preliminary results also indicate a perturbation of condensin I-related DNA damage responses. Thus, autophagy deficiency may result in dysregulation of condensin I which causes both aberrant mitotic condensation and compromised DNA repair mechanisms, both of which contribute greatly to genomic instability.